Evaluating maximum photovoltaic integration in district distribution systems considering optimal inverter dispatch and cloud shading conditions - Ding, Tao; Kou, Yu; Yang, Yongheng; Zhang, Yiyang; Yan, Huan; Blaabjerg, Frede (IET renewable power generation, 2017)
As photovoltaic (PV) integration increases in distribution systems, to investigate the maximum allowable PV integration capacity for a district distribution system becomes necessary in the planning phase, an optimisation model is thus proposed to evaluate the maximum PV integration capacity while guaranteeing the entire system operating constraints (e.g. network voltage magnitude) within reasonable ranges in this study. Meanwhile, optimal inverter dispatch is employed to further improve the PV integration by ensuring the optimal set-points of both active power and reactive power for the PV inverters. However, the intermittency of solar PV energy (e.g. due to passing clouds) may affect the PV generation in the district distribution network. To address this issue, the voltage magnitude constraints under the cloud shading conditions should be taken into account in the optimisation model, which can be formulated as a mixed integer non-linear non-convex programming. Furthermore, a sequential interior-point method is utilised to solve this problem. Case studies on the IEEE 33-bus, 69-bus distribution networks and two practical distribution networks in China demonstrate the effectiveness of the proposed method.